Research and analysis on the status quo of traditional villages in Guangxi Province based on Cite-space - Yuan, Tianyuan (International Journal of Global Economics and Management, 2024)
There are many well-preserved traditional ancient buildings in Guangxi Province, and the visualization of the academic achievements in this field can help to form a clear understanding of the current research status and development trend, so as to provide reference value for the subsequent research work. In this paper, we use Cite-space visualization software to systematically sort out 317 CNKI journals with the theme of "traditional villages in Guangxi" from the perspectives of literature characteristics and literature content, and find that: the number of published journals on the whole shows a rising trend, but is still relatively small; the academic atmosphere of mutual cooperation among journal authors is still good; the academic atmosphere of included journals is still good; the number of published journals is still small; and the number of published journals is still very small, and the academic atmosphere is still very small. The academic atmosphere among journal authors is still good; the included journals are mainly regional and ethnic, highlighting the specialization of regional nature research; the research hotspots are focused on traditional villages, rural revitalization, tourism development, urbanization and other fields, and future research should be combined with rural revitalization and rural tourism, and more consideration should be given to the development mode of rural revitalization by virtue of the characteristics of the traditional villages and the use of the tourism industry to promote rural revitalization, which is not only in line with the strategic planning of the country but also can better protect and inherit the traditional villages, but also can better protect and inherit the traditional villages. It can also better protect and inherit traditional culture.